Strontium Carbonate and Strontium-Substituted Calcium Carbonate Nanoparticles Form Protective Deposits on Dentin Surface and Enhance Human Dental Pulp Stem Cells Mineralization - Dotta, Tatiane Cristina; Hayann, Larwsk; de Padua Andrade Almeida, Leonardo; Nogueira, Lucas Fabrício B.; Arnez, Mayara M.; Castelo, Raisa; Cassiano, Ana Flávia B. [UNESP]; Faria, Gisele [UNESP]; Martelli-Tosi, Milena; Bottini, Massimo; Ciancaglini, Pietro; Catirse, Alma B. C. E. B.; et al. (MDPI, 2022)
Strontium acetate is applied for dental hypersensitivity treatment; however, the use of strontium carbonates for this purpose has not been described. The use of Sr-carbonate nanoparticles takes advantage of both the benefits of strontium on dentin mineralization and the abrasive properties of carbonates. Here in, we aimed to synthesize strontium carbonate and strontium-substituted calcium carbonate nanoparticles and test them as potential compounds in active dentifrices for treating dental hypersensitivity. For this, SrCO3, Sr0.5Ca0.5CO3, and CaCO3 nanoparticles were precipitated using Na2CO3, SrCl2, and/or CaCl2 as precursors. Their morphology and crystallinity were evaluated by electron microscopy (SEM) and X-ray diffraction, respectively. The nanoparticles were added to a poly (vinyl alcohol) gel and used to brush dentin surfaces isolated from human third molars. Dentin chemical composition before and after brushing was investigated by infrared spectroscopy (FTIR) and X-ray dispersive energy spectroscopy. Dentin tubule morphology, obliteration, and resistance of the coatings to acid attack were investigated by SEM and EDS. The cytotoxicity and ability of the particles to trigger the mineralization of hDPSCs in vitro were studied. Dentin brushed with the nanoparticles was coated by a mineral layer that was also able to penetrate the tubules, while CaCO3 remained as individual particles on the surface. FTIR bands related to carbonate groups were intensified after brushing with either SrCO3 or Sr0.5Ca0.5CO3. The shift of the phosphate-related FTIR band to a lower wavenumber indicated that strontium replaced calcium on the dentin structure after treatment. The coating promoted by SrCO3 or Sr0.5Ca0.5CO3 resisted the acid attack, while calcium and phosphorus were removed from the top of the dentin surface. The nanoparticles were not toxic to hDPSCs and elicited mineralization of the cells, as revealed by increased mineral nodule formation and enhanced expression of COL1, ALP, and RUNX2. Adding Sr0.5Ca0.5CO3 as an active ingredient in dentifrices formulations may be commercially advantageous since this compound combines the well-known abrasive properties of calcium carbonate with the mineralization ability of strontium, while the final cost remains between the cost of CaCO3 and SrCO3. The novel Sr0.5Ca0.5CO3 nanoparticles might emerge as an alternative for the treatment of dental hypersensitivity.
Keywords: biomaterials; dental hypersensivity; dentin; mineralization; strontium-containing nanoparticles